2002
DOI: 10.1177/0095327x0202900105
|View full text |Cite
|
Sign up to set email alerts
|

Warfare and Welfare: Military Service, Combat, and Marital Dissolution

Abstract: This article investigates the impact of military service on the duration of a veteran's first marriage, a topic in the literature with both scant and highly contradictory conclusions. Our sample consisted of 3,800 males from the National Survey of Families and Households (1987-1994). Using hazard rate analysis, we estimate the impact of both combat and noncombat assignments on marital duration. Our statistical results imply: (1) self-reported participation in combat increases the hazard rate for marital dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 0 publications
1
39
1
Order By: Relevance
“…Trauma, specifically combat or other military-related traumatic experiences, may be particularly detrimental couple and family functioning (Dekel & Monson, 2010;Dirkzwager et al, 2005;Ruger, Wilson, & Waddoups, 2002). Research by Riggs, Byrne, Weathers, and Litz (1998) indicated that over 70% of the PTSD veterans and their partners reported clinically significant levels of relationship distress, compared to 30% of the non-PTSD couples.…”
Section: Interpersonal Impact Of Traumamentioning
confidence: 99%
“…Trauma, specifically combat or other military-related traumatic experiences, may be particularly detrimental couple and family functioning (Dekel & Monson, 2010;Dirkzwager et al, 2005;Ruger, Wilson, & Waddoups, 2002). Research by Riggs, Byrne, Weathers, and Litz (1998) indicated that over 70% of the PTSD veterans and their partners reported clinically significant levels of relationship distress, compared to 30% of the non-PTSD couples.…”
Section: Interpersonal Impact Of Traumamentioning
confidence: 99%
“…For example, although service in the Vietnam War has not been associated with higher rates of divorce, those who had greater exposure to combat during their service in that war also experienced higher rates of marital problems after their service. Using retrospective life-history data from the National Survey of Families and Households, Ruger, Wilson, and Waddoups (2002) estimated that, controlling for background and period of service, the experience of military combat in any war between 1930 and 1984 increased the risk of subsequent marital dissolution by 62 percent. Thus, whereas any deployment is stressful, it may only be exposure to combat that has the lasting effects on service members that lead to the deterioration of marriages.…”
Section: Understanding the Effects Of Military Service And Deploymentmentioning
confidence: 99%
“…Until models of military marriage are refined enough to take the changing social context of the military into account, assumptions based on prior research should be examined with caution. These issues have rarely been acknowledged in contemporary research on military marriage (see Ruger, Wilson, and Waddoups, 2002, for a rare exception).…”
Section: Infrequent Acknowledgment Of Cohort Effectsmentioning
confidence: 99%
“…Although links between combat and marital outcomes are reported in U.S. research (Ruger, Wilson, & Waddoups, 2002), the retrospective methods and focus on historical wars in these studies makes generalizing to the recent conflicts in Iraq and Afghanistan questionable. More recent research shows that combat exposure is unrelated to marital quality (Renshaw, Rodrigues, & Jones, 2008;Riviere, Merrill, Thomas, Wilk, & Bliese, 2012).…”
Section: Combat Exposurementioning
confidence: 99%